Conservation law in Antarctica and the Southern Ocean: the Antarctic Treaty System, conservation, and environmental protection - Anthony Press; Andrew Constable (2022)
The Antarctic Treaty System provides the corpus of law that governs the obligations of its Parties to protect and conserve the Antarctic environment. The System consists principally of the Antarctic Treaty (the Treaty), the Convention on the Conservation of Antarctic Marine Living Resources (CAMLR Convention), and the Protocol on Environmental Protection to the Antarctic Treaty (Environmental Protocol). The Antarctic Treaty establishes the Antarctic Treaty Consultative Meeting – the body that makes decisions under the provisions of the Treaty and Environmental Protocol. The CAMLR Convention establishes the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) – its decision-making body. Together, these two international bodies are responsible for the modern-day conservation and environmental management regimes for Antarctica and the Southern Ocean. This paper looks at the scope of law developed under the Antarctic Treaty System and its evolution; and at the interaction between the different components of the Antarctic Treaty System. The paper also forecasts some of the future challenges to conservation and environmental protection in Antarctica and the Southern Ocean.